2014
DOI: 10.1089/hum.2013.009
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus Glycoprotein– and Venezuelan Equine Encephalitis Virus-Derived Glycoprotein–Pseudotyped Lentivirus Vectors Differentially Transduce Corneal Endothelium, Trabecular Meshwork, and Human Photoreceptors

Abstract: The ability to deliver a large transgene efficiently to photoreceptors using viral vectors remains problematic and yet is critical for the future therapy of inherited retinal diseases such as Stargardt's and Usher's 1B. Herein, we examine the ocular tropism of a HIV-1-based lentivirus vector pseudotyped with Venezuelan equine encephalitis virus-derived glycoprotein (VEEV-G) after intraocular delivery to the posterior and anterior chambers of C57BL/6 wild-type mice. Reporter gene (EGFP) expression was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
18
0
2
Order By: Relevance
“…However, HIV-1-Mokola and Ross River Virus (HIV-1-RRV) were shown to transduce only RPE after subretinal delivery (Auricchio et al, 2001; Bemelmans et al, 2005; Greenberg et al, 2007). Recently, HIV-1-based vectors pseudotyped with the Venezuelan Equine Encephalitis Virus-derived glycoprotein (VEEVG) were shown to transduce murine RPE after subretinal delivery (Lipinski et al, 2014), although degeneration of the ONL was observed with this pseudotype. A LV vector based on the HIV-2 genome was reported to transduce PR after subretinal injection in adult rabbits (Cheng et al, 2002).…”
Section: Lentiviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HIV-1-Mokola and Ross River Virus (HIV-1-RRV) were shown to transduce only RPE after subretinal delivery (Auricchio et al, 2001; Bemelmans et al, 2005; Greenberg et al, 2007). Recently, HIV-1-based vectors pseudotyped with the Venezuelan Equine Encephalitis Virus-derived glycoprotein (VEEVG) were shown to transduce murine RPE after subretinal delivery (Lipinski et al, 2014), although degeneration of the ONL was observed with this pseudotype. A LV vector based on the HIV-2 genome was reported to transduce PR after subretinal injection in adult rabbits (Cheng et al, 2002).…”
Section: Lentiviral Vectorsmentioning
confidence: 99%
“…Although LV-VSVG vector binding seemed independent of specific cell surface receptors (Coil and Miller, 2004), studies carried out in adult murine retinal explants, which lack physical barriers since they are compromised during the process of explantation, have shown that LV-VSVG cannot transduce PR (Lipinski et al, 2014). Surprisingly, limited PR transduction was observed in a human retinal explant transduced with LV-VSVG, suggesting that transduction may be species-dependent (Lipinski et al, 2014). …”
Section: Lentiviral Vectorsmentioning
confidence: 99%
“…The later development of a modified replication-deficient HIV-derived retroviral vector allowed the transduction of non-dividing cells 99 and was subsequently shown to successfully target photoreceptors and RPE cells, cornal endothelium and trabecular meshwork 43,100,101 . However the percentage of transduced mouse photoreceptors after lentiviral gene delivery still remains higher in newborn retinas compared to adult mice 102 .…”
Section: Technological Innovation For Current Hurdlesmentioning
confidence: 99%
“…De nombreuses études montrent que, lorsqu'ils sont injectés par voie sous-rétinienne, les lentivirus transduisent efficacement l'épithélium rétinien pigmentaire chez les rongeurs [15,16], mais la transduction des photorécepteurs reste variable [17,18]. L'efficacité de transduction des photorécepteurs par les lentivirus dépend de l'origine du lentivirus et de l'espèce étudiée [19]. Par exemple, les lentivirus d'origine équine donnent de bons résultats de transduction des photorécepteurs situés à proximité du site d'injection chez le primate non humain [19,20].…”
Section: Les Lentivirusunclassified
“…L'efficacité de transduction des photorécepteurs par les lentivirus dépend de l'origine du lentivirus et de l'espèce étudiée [19]. Par exemple, les lentivirus d'origine équine donnent de bons résultats de transduction des photorécepteurs situés à proximité du site d'injection chez le primate non humain [19,20]. Deux essais cliniques sont en cours pour traiter la 3 épisomale (pour le virus recombinant).…”
Section: Les Lentivirusunclassified